Carotid artery intima-media thickness and hypertensive heart disease: a short review - Costan G. Magnussen (BMC, 2017)
Abstract Sustained by its relative ease of assessment, carotid artery intima-media thickness (cIMT) has emerged as an important surrogate marker of target organ damage in hypertensive heart disease over the last three decades. However, the prognostic utility of cIMT in hypertensive heart disease differs depending on its application. This review outlines cIMT and its prognostic utility among patients with hypertensive heart disease. It provides an overview of limitations of cIMT and areas for future research.